Self-Management Support to People with Type 2 Diabetes - A comparative study of Kaiser Permanente and the Danish Healthcare System - Schiøtz Michaela; Strandberg-Larsen Martin; Frølich Anne; Krasnik Allan; Bellows Jim; Kristensen Jette K; Vedsted Peter; Eskildsen Peter; Beck-Nielsen Henning; Hsu John (BMC, 2012)
Abstract Background Self-management support is considered to be an essential part of diabetes care. However, the implementation of self-management support within healthcare settings has appeared to be challenging and there is increased interest in "real world" best practice examples to guide policy efforts. In order to explore how different approaches to diabetes care and differences in management structure influence the provision of SMS we selected two healthcare systems that have shown to be comparable in terms of budget, benefits and entitlements. We compared the extent of SMS provided and the self-management behaviors of people living with diabetes in Kaiser Permanente (KP) and the Danish Healthcare System (DHS). Methods Self-administered questionnaires were used to collect data from a random sample of 2,536 individuals with DM from KP and the DHS in 2006-2007 to compare the level of SMS provided in the two systems and identify disparities associated with educational attainment. The response rates were 75 % in the DHS and 56 % in KP. After adjusting for gender, age, educational level, and HbA1c level, multiple linear regression analyses determined the level of SMS provided and identified disparities associated with educational attainment. Results Receipt of SMS varied substantially between the two systems. More people with diabetes in KP reported receiving all types of SMS and use of SMS tools compared to the DHS (p < .0001). Less than half of all respondents reported taking diabetes medication as prescribed and following national guidelines for exercise. Conclusions Despite better SMS support in KP compared to the DHS, self-management remains an under-supported area of care for people receiving care for diabetes in the two health systems. Our study thereby suggests opportunity for improvements especially within the Danish healthcare system and systems adopting similar SMS support strategies.